Composite powder particle of self-protection open arc surfacing high-boron alloy and application method

By preparing a combined surfacing technology of composite powder particles with suitable particle size and ER304 stainless steel solid welding wire, austenite-based high-boron alloy is formed, including a variety of hard phases, and the high-boron alloy is solved under the conditions of bright arc surfacing. The crack resistance and wear resistance problems significantly improve microhardness and wear performance.

CN119188015APending Publication Date: 2024-12-27XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493887.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing high-boron alloys are prone to cracking under the conditions of bright arc welding, and brittle abnormal eutectic precipitation leads to insufficient crack resistance, and the chromium content is limited, making it difficult to improve wear resistance, especially in medium-temperature environments with poor wear performance.

Method used

Use composite powder particles with particle sizes of 8 mesh to 10 mesh, containing ferromolybdenum, boron carbide, high-carbon ferrochromium, titanium iron, aluminum-magnesium powder and reduced iron powder. It is weighed through sieve, dry powder mixing, wet powder mixing, rotary production Preparation of particles and low-temperature sintering, combined with ER304 stainless steel solid welding wire for self-protection and open arc surfacing, forming a high-boron alloy mainly composed of austenite, including Mo2FeB2, M2B, M23(C,B)6 and TiC phases, optimizing chromium atoms Source and distribution of carbon and boron.

Benefits of technology

The microhardness reaches 1070~1666HV, which significantly improves crack resistance and wear resistance, overcomes the disadvantages of a single M2B phase, is suitable for medium-temperature wear conditions, has a wear weight lower than that of traditional high-boron alloys, and has high toughness and excellent wear resistance. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119188015A_ABST
    Figure CN119188015A_ABST
Patent Text Reader

Abstract

The invention relates to a composite powder particle of a self-protection open arc surfacing high-boron alloy. The composite powder particle with the particle size of 8-10 meshes is prepared by the following preparation process steps: screening and weighing powder components contained in the composite powder particle, carrying out dry powder mixing, adding water glass, carrying out wet powder mixing, carrying out wet powder rotary granulation, sintering at low temperature and screening the powder particle. And the composite powder particles and the ER304 solid welding wire are used for self-protection open arc surfacing, so that the composite powder particle melt and the solid welding wire molten drops jointly form a surfacing molten pool and are solidified into the high-boron alloy. The alloy component types and content of the composite powder particles are optimized, so that the distribution and number of carbon atoms and boron atoms in a wear-resistant phase and a matrix are regulated and controlled, an organization structure synergistically strengthened by a blocky main wear-resistant phase comprising a Mo2FeB2 phase and an M2B phase, a strip-shaped M23 (C, B) 6 phase, a point-shaped TiC phase and an austenite matrix is formed, and the microhardness of the surfacing alloy can reach 1500-1700 HV. The composite powder particles can be used for surfacing alloy layers which bear impact loads and resist medium-temperature abrasive particle abrasion on parts, such as surfacing preparation and repair of tooth heads of single-roll crushers for crushing high-temperature slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wear-resistant surfacing, and in particular relates to composite powder particles for self-protected open arc surfacing of high-boron alloy and an application method thereof. Background Art

[0002] In industrial applications, iron-based wear-resistant alloys are the most widely used, mainly due to their high cost-effectiveness and popularity among users. There are two main types: high chromium and high boron alloys. High boron alloys are prone to precipitate a large number of tetrahedral blocky Fe2B-type borides because the solubility of boron atoms in matrices such as ferrite and austenite is less than 0.02%, thus showing higher wear resistance. Common high boron alloy systems include Fe-B, Fe-CB, Fe-Cr-B, Fe-Cr-BC, etc.

[0003] In order to improve the self-protection process performance of surfacing materials such as flux-cored welding wires and composite powders, a certain amount of carbon-containing components is usually added, part of which is added in the form of composite carbon such as high-carbon ferrochrome, and the other part is added in the form of single substances such as graphite. Replacing the "metal chromium + graphite" method with composite carbon such as high-carbon ferrochrome can reduce the cost of surfacing materials, increase the amount of self-generated protective gas and improve the surfacing process performance. Adding it in the form of graphite can also improve the self-protection process performance. However, no matter which of the above methods is used to add carbon components, a large amount of abnormal eutectics (α-Fe+M3(B,C)) will be precipitated. These abnormal eutectics are either honeycomb-shaped or intergranular network-shaped, and are very brittle as a whole, which greatly reduces the toughness of high-boron alloys, causing them to crack easily under open arc surfacing conditions and show peeling and falling. This requires suppressing the precipitation of brittle abnormal brittleness to improve its crack resistance.

[0004] The main wear-resistant phase of high-boron alloy is Fe2B, in which Cr atoms replace Fe atoms to obtain a composite (Fe,Cr)2B phase. Studies have shown that increasing the chromium content of this phase can improve its microhardness and phase toughness and reduce the tendency to embrittlement. However, due to the addition of a large number of boron-containing components, there is a lack of space in the surfacing material to prepare a high-boron alloy with a high chromium content, resulting in the chromium content being limited to less than 12% Cr and making it difficult to improve the properties of the (Fe,Cr)2B phase. It is imperative to innovate the way of adding chromium components. Not only that, the medium-temperature phase strength of the (Fe,Cr)2B phase is insufficient, and it is more urgent to prepare a new medium- and high-temperature wear-resistant phase.

[0005] The matrix of high-boron alloy is mainly ferrite or a certain amount of chromium-rich ferrite with a solid solution, less martensite, and this series of alloys are brittle. High-boron alloys with austenite matrix are difficult to obtain, mainly because there is no space to add a large amount of austenitized alloy components in the surfacing material, which makes it difficult for the crack resistance of high-boron alloys to meet actual requirements.

[0006] Therefore, a composite powder particle for surfacing a high-boron alloy with austenite as a matrix is ​​developed, and the surfacing alloy is made to have both excellent wear resistance and high crack resistance. Summary of the invention

[0007] One of the purposes of the present invention is to provide a composite powder for self-shielded open arc surfacing of high-boron alloy in view of the above-mentioned deficiencies of current surfacing materials.

[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0009] The composite powder particles are prepared by the following steps: weighing the powder components contained therein, dry mixing, adding water glass to wet mixing, wet powder rotary granulation, low temperature sintering, and powder particle screening to form composite powder particles with a particle size of 8 to 10 meshes;

[0010] The weight percentages of the powder components contained in the composite powder particles are: 37-42% of ferromolybdenum (FeMo50-A) with a molybdenum content of 48-52%; 20-22% of boron carbide (B4C) with a boron carbide content of more than 99%; 10-12% of high-carbon ferrochromium (FeCr70C8.0-A) with a chromium content of 68-72% and a carbon content of 8%; 9-11% of ferrotitanium (FeTi30-A) with a titanium content of 25-30%; 2-3% of aluminum-magnesium powder (Al-Mg) with an aluminum content of 49-50% and a magnesium content of 49-50%; and the remainder is reduced iron powder (Fe) with an iron content of not less than 98%.

[0011] Furthermore, the powder components of ferromolybdenum, boron carbide, high carbon ferrochromium, ferrotitanium and reduced iron powder contained in the composite powder particles are passed through a 60-mesh sieve, and the aluminum-magnesium powder is passed through a 200-mesh sieve and then weighed.

[0012] Furthermore, the water glass added to the dry mixed powder is of sodium silicate type, with a Baume degree of 30 to 35 and a modulus of 3.0 to 3.3.

[0013] Furthermore, water glass was added to the dry mixed powder so as to be 20 to 25 ml of sodium silicate type water glass per 100 g of the dry mixed powder, and wet mixing was performed.

[0014] Furthermore, the rotation speed of the wet powder for bonding and granulation is 2 to 4 revolutions per second.

[0015] Furthermore, the composite powder particles are sintered at a low temperature of 280-300° C. and kept at this temperature for 2-4 hours before being taken out of the furnace.

[0016] The second object of the present invention is to provide an application method of the above-mentioned composite powder particles, namely: before welding, the screened composite powder particles are pre-placed on the weld, and an ER304 stainless steel solid welding wire with a diameter of Φ2.5mm (the chemical composition of this type of welding wire is equivalent to the H0Cr18Ni9 welding wire listed in the national standard GB / T17854-99) is used as a filling material. A DC power supply reverse connection method is used for self-shielded open arc surfacing welding. The arc generated between the stainless steel solid welding wire and the substrate is used to melt the composite powder particles pre-placed on the weld, and the composite powder particles are melted together with the stainless steel solid welding wire to form a surfacing pool, which is cooled and solidified into a high boron alloy with a powder filling rate (powder filling rate = composite powder particle melt weight / (composite powder particle melt weight + ER304 stainless steel solid welding wire melt weight)) of 0.45 to 0.50.

[0017] Furthermore, the surfacing welding current control value is 410-420A, and the welding machine trolley travel speed is 15.5-16.0m / h.

[0018] The composite powder of the present invention is used in conjunction with ER304 stainless steel solid welding wire to surfacing high boron alloy; the alloy matrix is ​​mainly austenite and also includes a small amount of ferrite; the hard phase includes block Mo2FeB2 phase (M includes two main alloying elements Fe and Cr, the same below), block M2B phase, thin strip M 23 (C,B)6 phase, dot-like TiC phase and Fe4N phase (this phase is small in size and mainly distributed in the austenite matrix), forming a plastic matrix and a high-hardness wear-resistant phase synergistically strengthened organizational structure. The composite powder can be used for surfacing wear-resistant alloys of parts with certain impact loads and medium-temperature abrasive wear conditions, such as the surfacing preparation and repair of the tooth head and side of a single-roll crusher that crushes high-temperature slag.

[0019] Compared with the prior art, the present invention has the following innovative features and beneficial effects:

[0020] (1) High crack resistance: Austenite is the main matrix, which not only dissolves a high content of carbon, but also avoids the precipitation of the modified eutectic (α-Fe+M3(B,C)), thereby improving the crack resistance of the open arc high-boron weld. In addition, austenite has a face-centered cubic structure with many slip systems. Through its plastic deformation, it can effectively reduce the impact of the external load on the main wear-resistant M2B phase of the high-boron alloy, and no cracks are generated in the two layers of self-protected open arc cladding.

[0021] (2) The sources of chromium atoms are different: Unlike the chromium atoms of conventional high-boron alloys, which mainly come from chromium-containing components such as metallic chromium, high-carbon ferrochrome or low-carbon ferrochrome contained in the composite powder particles, the chromium atoms of the high-boron alloy mainly come from the ER304 stainless steel solid welding wire. The composite powder particles supplement some chromium atoms, which makes the chromium content of the high-boron alloy exceed 12% Cr, leaving enough operating space for adding other alloy components to precipitate another main wear-resistant phase, and the overall alloy presents high corrosion resistance, which is conducive to improving wear resistance.

[0022] (3) Different main wear-resistant phases: Unlike the usual high-boron alloys which only have a blocky M2B phase, the main wear-resistant phases of the high-boron alloy include blocky Mo2FeB2 phases and blocky M2B phases, overcoming the shortcomings of the original single M2B phase; the Mo2FeB2 phase has higher microhardness and high temperature resistance than the M2B phase, which makes the high-boron alloy can be used in medium-temperature abrasive wear conditions.

[0023] (4) The microhardness of the high-boron alloy layer is high: the microhardness of the first layer of the high-boron alloy layer is 1070-1167 HV; the microhardness of the second layer is 1384-1666 HV, which is higher than the average microhardness of the traditional high-boron alloy of about 1200 HV, reaching the level of powder carbide tools. In particular, the microhardness of the second layer has surpassed the microhardness of the blocky M2B phase contained in the general high-boron alloy.

[0024] (5) Excellent wear resistance: The average wear loss of the prepared wear-resistant alloy is 0.0044g, which is much lower than the 0.03-0.05g wear loss of general high-chromium and high-boron alloys, showing extremely excellent wear resistance; the alloy also has good crack resistance, and has the special properties of high toughness and extremely excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the microstructure diagram of the high boron alloy prepared in Example 1.

[0026] Figure 2 This is the phase composition diagram of the high boron alloy prepared in Example 1.

[0027] Figure 3 This is the microstructure diagram of the high boron alloy prepared in Comparative Example 1.

[0028] Figure 4 This is the phase composition diagram of the high boron alloy prepared in Comparative Example 1.

[0029] Figure 5 for Figure 1 The wear morphology of the high boron alloy prepared in Example 1 is shown.

[0030] Figure 6 for Figure 3The wear morphology of the high boron alloy prepared in Comparative Example 1 is shown.

[0031] Figure 7 1 is a microhardness distribution diagram of the vertical cross section of the high boron alloy layer of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the embodiments of the present invention are not limited thereto.

[0033] The composite powder particles of the present invention are prepared by the following preparation process steps: weighing the powder components contained therein, dry mixing, adding water glass to wet mixing, wet powder rotary granulation, low temperature sintering, and powder particle screening to prepare composite powder particles with a particle size of 8 to 10 meshes;

[0034] The weight percentages of the powder components contained in the composite powder particles are: 37-42% of ferromolybdenum (FeMo50-A) with a molybdenum content of 48-52%; 20-22% of boron carbide (B4C) with a boron carbide content of 99-100%; 10-12% of high-carbon ferrochromium (FeCr70C8.0-A) with a chromium content of 68-72% and a carbon content of 8%; 9-11% of ferrotitanium (FeTi30-A) with a titanium content of 25-30%; 2-3% of aluminum-magnesium powder (Al-Mg) with an aluminum content of 49-50% and a magnesium content of 49-50%; and the remainder is reduced iron powder (Fe) with an iron content of not less than 98%.

[0035] Before weighing the components, the powder components of ferromolybdenum, boron carbide, high carbon ferrochromium, ferrotitanium, and reduced iron powder are first sieved through a 60-mesh sieve, and the aluminum and magnesium powders are sieved through a 200-mesh sieve before being weighed; then the powder components are weighed according to the composition ratio of the composite powder particles, and then all the powder components are placed in the same container and stirred thoroughly to mix evenly to form a dry mixed powder.

[0036] Following the previous step, add sodium silicate water glass with a Baume degree of 30 to 35 and a modulus of 3.0 to 3.3 to the dry mixed powder by pouring 3 to 6 ml each time, until every 100 g of the above dry mixed powder finally contains 20 to 25 ml of water glass; during the addition, stir continuously to allow the water glass to evenly infiltrate the mixed powder, then rotate the container at a speed of 2 to 4 rpm to rotate and bond the wet powder into spherical wet powder particles, and let it stand for more than 5 minutes to set.

[0037] Next, the spherical wet composite powder particles are placed in a sintering furnace, heated to 280-300° C., kept at this temperature for 2-4 hours, and then taken out of the furnace.

[0038] Then, the sintered composite powder particles are first passed through an 8-mesh sieve to remove large particles larger than 8 mesh; then passed through a 10-mesh sieve to remove small particles smaller than 10 mesh, and finally composite powder particles with a particle size of 8 to 10 mesh are obtained.

[0039] On a Q235A steel plate with a length of 160mm×width of 75mm×thickness of 20mm, composite powder particles are pre-placed on the weld before welding, and an ER304 stainless steel solid welding wire with a diameter of Φ2.5mm is used as the filling material. The arc generated between the solid welding wire and the substrate is used to melt the composite powder particles pre-placed on the weld, and the composite powder particles and the molten droplets of the stainless steel solid welding wire are melted to form a surfacing pool, which is cooled and solidified into a high-boron alloy with a powder filling rate of 0.45 to 0.50.

[0040] Before surfacing, the polarity of the automatic welding machine ZD5-1000E was set to DC reverse connection, the current setting value was 410-420A, the arc voltage was 30-35V, the welding wire extension length was 30-35mm, the trolley travel speed was 15.5-16.0m / h, and the surfacing process parameters of each layer remained unchanged.

[0041] Self-shielded open arc welding is performed using the above-mentioned composite powder and ER304 stainless steel solid welding wire as surfacing materials, so that the composite powder melt and the ER304 stainless steel solid welding wire molten droplets are fused into a surfacing molten pool. After the molten pool is cooled and solidified, the first layer of weld is formed. It is air-cooled to room temperature, and a small amount of slag on the weld surface is cleaned; then the second layer is surfacing in the same way.

[0042] Based on this, the design principle of a composite powder and an application method for self-protected open arc surfacing of high-boron alloys of the present invention can be summarized as follows: first prepare composite powder with a particle size of 8 to 10 meshes, use the composite powder and ER304 stainless steel solid welding wire as filling materials, perform self-protected open arc surfacing, and fuse the composite powder melt and the solid welding wire molten droplet into a surfacing pool and solidify into a high-boron alloy; at the same time, by utilizing the relatively strong binding ability of Mo and B atoms, the strong affinity of Ti for C atoms, the relatively strong affinity of Cr for B atoms, and the large difference in atomic radius between C atoms and B atoms and the difference in their austenite solubility, the types and contents of alloy components of the composite powder are continuously optimized to regulate the distribution and quantity of carbon atoms and boron atoms in the wear-resistant phase and the matrix, and effectively separate the boron atoms and carbon atoms melted and decomposed by the B4C particles, thereby optimizing the B / C component distribution and precipitating primary blocky Mo2FeB2 phase and blocky M2B phase; and the boron atoms diffused into the austenite matrix and the carbon atoms are precipitated together to form M 23 (C, B)6 phase, the excess carbon atoms are dissolved in the austenite matrix, enhancing its stability and making it difficult to transform; the in-situ precipitated TiC phase is dispersed and distributed with the strip M 23 The (C, B)6 phases jointly strengthen the austenite matrix, giving it a higher strength. It can be seen that the high-boron alloy as a whole constructs a synergistically strengthened organizational structure of a plastic matrix and a high-hardness wear-resistant phase, which gives it higher crack resistance and extremely excellent wear resistance.

[0043] Example 1

[0044] Before weighing the components, the powder components such as ferromolybdenum, boron carbide, high carbon ferrochrome, ferrotitanium, and reduced iron powder are first sieved through a 60-mesh sieve, and then the aluminum and magnesium powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: 38% ferromolybdenum, 21% boron carbide, 10% high carbon ferrochrome, 11% ferrotitanium, 2.5% aluminum and magnesium powder, and 17.5% reduced iron powder.

[0045] According to the powder content contained in the above-mentioned composite powder particles, powder components such as molybdenum iron, boron carbide, high carbon ferrochrome, titanium iron, aluminum magnesium powder and reduced iron powder are weighed, and then all the weighed powder components are placed in the same container, and are fully dry-stirred to mix the powders evenly to form a dry mixed powder.

[0046] Next, 5 ml of sodium silicate water glass with a Baume degree of 30 and a modulus of 3.3 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 20 ml of water glass is finally added to every 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 4 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is slightly vibrated, and then the container is rotated until most of the composite powder particles have a uniform size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;

[0047] Next, the composite powder particles are placed in a sintering furnace and heated to 288°C, and then taken out of the furnace after being kept at this temperature for 4 hours. Then, the sintered composite powder particles are first sieved through an 8-mesh sieve to remove large particles larger than 8 mesh, and then sieved through a 10-mesh sieve to remove small particles smaller than 10 mesh, and finally composite powder particles with a particle size of 8 to 10 mesh are obtained.

[0048] Finally, on a Q235A steel plate with a length of 160 mm, a width of 75 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned sieved composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated to obtain a surfacing alloy with a powder filling rate of 0.48.

[0049] Before surfacing, the polarity of the automatic welding machine ZD5-1000E was set to DC reverse connection, and the surfacing process parameters were shown in Table 1.

[0050] The composite powder particles and ER304 stainless steel solid wire after sintering and sieving are used as filling materials for self-shielded open arc welding. The arc generated between the welding wire and the substrate is used to melt the composite powder particles and melt with the ER304 stainless steel solid wire droplets to form a surfacing molten pool. After the molten pool is air-cooled and solidified to form the first layer of weld, a small amount of slag on the surface is removed; then, the second layer is surfacing in the same way. After welding, the weld surface is bright without defects such as cracks and pores.

[0051] Table 1 Composite powder and ER304 stainless steel solid wire surfacing process parameters

[0052]

[0053] The surfacing weld samples were processed by wire cutting method to prepare wear-resistant samples with specifications of 57mm×25.5mm×6mm.

[0054] The wear resistance test was conducted using an MLS-225B wet sand rubber wheel wear tester. The test conditions were as follows: the rubber wheel had a diameter of 178 mm and a hardness of 60 Shore, the added weight was 2.5 kg, the rubber wheel speed was 240 rpm, and the mortar ratio was 1500 g of quartz sand of 40-60 mesh with 1000 g of tap water. The sample was pre-grinded for 1000 revolutions, rinsed, dried, and weighed at an initial weight of M0. After the formal test was conducted for 1000 revolutions, it was cleaned and dried, and weighed at M1. The absolute weight loss of the sample after wear was ΔM=M0-M1.

[0055] The high-boron alloy prepared in Example 1 is used as a standard sample. The relative wear coefficient ε=absolute weight loss of the standard sample / absolute weight loss of the sample. The test results are shown in Table 2.

[0056] The microstructure, phase composition and wear morphology of the cladding high boron alloy of Example 1 are shown in the attached drawings. Figure 1 , Attachment Figure 2 and attached Figure 5 The microscopic distribution diagram of the vertical section of the surfacing high boron alloy layer is shown in the attached figure. Figure 7 shown.

[0057] Example 2

[0058] Before weighing the components, the powder components such as ferromolybdenum, boron carbide, high carbon ferrochrome, ferrotitanium, and reduced iron powder are first sieved through a 60-mesh sieve, and then the aluminum and magnesium powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: ferromolybdenum 42%, boron carbide 20%, high carbon ferrochrome 12%, ferrotitanium 10%, aluminum and magnesium powder 3%, and reduced iron powder 13%.

[0059] According to the powder content contained in the above-mentioned composite powder particles, powder components such as molybdenum iron, boron carbide, high carbon ferrochrome, titanium iron, aluminum magnesium powder and reduced iron powder are weighed, and then all the weighed powder components are placed in the same container, and are fully dry-stirred to mix the powders evenly to form a dry mixed powder.

[0060] Next, 5 ml of sodium silicate water glass with a Baume degree of 32 and a modulus of 3.0 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 25 ml of water glass is finally added per 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 3 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is slightly vibrated, and then the container is rotated until most of the composite powder particles have a uniform size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;

[0061] Next, the composite powder particles are placed in a sintering furnace and heated to 295°C, and then taken out of the furnace after being kept at this temperature for 3 hours. Then, the sintered composite powder particles are first sieved through an 8-mesh sieve to remove large particles larger than 8 mesh; and then sieved through a 10-mesh sieve to remove small particles smaller than 10 mesh, and finally composite powder particles with a particle size of 8 to 10 mesh are obtained.

[0062] Finally, on a Q235A steel plate with a length of 160 mm, a width of 75 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned sieved composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated to obtain a surfacing alloy with a powder filling rate of 0.45.

[0063] The remaining steps and wear resistance test contents are the same as those in Example 1.

[0064] Example 3

[0065] Before weighing the components, the powder components such as ferromolybdenum, boron carbide, high carbon ferrochrome, ferrotitanium, and reduced iron powder are first sieved through a 60-mesh sieve, and then the aluminum and magnesium powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: ferromolybdenum 40%, boron carbide 22%, high carbon ferrochrome 12%, ferrotitanium 9%, aluminum and magnesium powder 2%, and reduced iron powder 15%.

[0066] According to the powder content contained in the above-mentioned composite powder particles, powder components such as molybdenum iron, boron carbide, high carbon ferrochrome, titanium iron, aluminum magnesium powder and reduced iron powder are weighed, and then all the weighed powder components are placed in the same container, and are fully dry-stirred to mix the powders evenly to form a dry mixed powder.

[0067] Next, 4 ml of sodium silicate water glass with a Baume degree of 35 and a modulus of 3.1 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 24 ml of water glass is finally added per 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 3 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is slightly vibrated, and then the container is rotated until most of the composite powder particles have a uniform size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;

[0068] Next, the composite powder particles are placed in a sintering furnace and heated to 280°C, and then taken out of the furnace after being kept at this temperature for 4 hours. Then, the sintered composite powder particles are first sieved through an 8-mesh sieve to remove large particles larger than 8 mesh; and then sieved through a 10-mesh sieve to remove small particles smaller than 10 mesh, and finally composite powder particles with a particle size of 8 to 10 mesh are obtained.

[0069] Finally, on a Q235A steel plate with a length of 160 mm, a width of 75 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned sieved composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated to obtain a surfacing alloy with a powder filling rate of 0.49.

[0070] The remaining steps and wear resistance test contents are the same as those in Example 1.

[0071] Comparative Example 1

[0072] Before weighing the components, the boron carbide, high carbon ferrochrome, ferrotitanium, reduced iron powder and other powder components are first sieved through a 60-mesh sieve, and then the aluminum and magnesium powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: 21% boron carbide, 10% high carbon ferrochrome, 11% ferrotitanium, 2.5% aluminum and magnesium powder, and 55.5% reduced iron powder.

[0073] According to the powder content contained in the above-mentioned composite powder particles, powder components such as molybdenum iron, boron carbide, high carbon ferrochromium, ferrotitanium, aluminum magnesium powder and reduced iron powder are weighed, and then all the weighed powder components are placed in the same container, and are fully dry-stirred to mix the powders evenly to form a dry mixed powder.

[0074] Next, 5 ml of sodium silicate water glass with a Baume degree of 30 and a modulus of 3.3 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 20 ml of water glass is finally added to every 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 4 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is slightly vibrated, and then the container is rotated until most of the composite powder particles have a uniform size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;

[0075] Next, the composite powder particles are placed in a sintering furnace and heated to 288°C, and then taken out of the furnace after being kept at this temperature for 4 hours. Then, the sintered composite powder particles are first sieved through an 8-mesh sieve to remove large particles larger than 8 mesh; and then sieved through a 10-mesh sieve to remove small particles smaller than 10 mesh, and finally composite powder particles with a particle size of 8 to 10 mesh are obtained.

[0076] Finally, on a Q235A steel plate with a length of 160 mm, a width of 75 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned sieved composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated to obtain a surfacing alloy with a powder filling rate of 0.48.

[0077] The surfacing welding process parameters, polarity setting and surfacing welding process of the automatic welding machine ZD5-1000E used in Comparative Example 1 are the same as those in Example 1. The wear resistance test content is the same as that in Example 1.

[0078] The microstructure, phase composition and wear morphology of the high boron alloy prepared by composite powder surfacing welding shown in Comparative Example 1 are as follows: Figure 3 , Figure 4 and Figure 7 As shown, the molybdenum-free high-boron alloy of Comparative Example 1 is used as a comparative sample.

[0079] It can be seen from Table 2 that the relative wear coefficient ε of the high boron alloy prepared by the composite powder surfacing of the present invention is 8.75 to 15.31 times that of the surfacing alloy of the composite powder without adding the molybdenum component, and the wear weight loss is much lower than the ordinary high boron alloy 0.03 to 0.05g, which shows that the high boron alloy prepared by the composite powder has extremely excellent wear resistance.

[0080] Table 2 Abrasive wear resistance of high boron alloys prepared by surfacing welding in comparative examples and embodiments

[0081]

[0082] By attaching Figure 1 and attached Figure 2 It can be seen that the high boron alloy structure prepared by using composite powder and ER304 stainless steel solid welding wire as welding materials is mainly composed of austenite (γ-Fe), ferrite (α-Fe(F)), Mo2FeB2 phase, M2B phase, M 23 It is composed of (C,B)6 phase, TiC and Fe4N phases.

[0083] In addition, the attached Figure 1 The microstructure under the backscattering condition shown in FIG. 1 shows that the main wear-resistant phases of the high-boron alloy prepared by the method of the present invention include gray blocky M2B phase and white blocky Mo2FeB2 phase. There are black dot-shaped in-situ precipitated TiC phases inside or on the edges of these two phases, which are surrounded by austenite with high plasticity. When subjected to external impact loads, the impact can be buffered and the impact force on the main wear-resistant phase can be reduced, thereby improving the crack resistance of the alloy. Strip-shaped M2B phases are distributed in the austenite matrix. 23(C,B)6 phase, which has a face-centered cubic structure, can form coherent or semi-coherent grain boundaries with the austenite matrix, which can not only strengthen the austenite, but also act as wear-resistant particles to improve wear resistance. 23 A small amount of ferrite matrix precipitated between the (C, B)6 phases. Figure 1 It is difficult to distinguish, but the Figure 2 The phase can be shown, but the characteristic diffraction peak is very weak, indicating that the volume fraction is extremely small. The average macroscopic hardness of the alloy is 65.5HRC, which has ultra-high macroscopic hardness. Figure 1 It shows that the high-boron alloy forms a synergistically strengthened structure of blocky wear-resistant phase, strip-shaped wear-resistant phase, point-shaped in-situ precipitation phase and austenite matrix.

[0084] The composite powder particles used in comparative example 1 differ from those in example 1 only in the presence or absence of ferromolybdenum, and the other components and surfacing processes are exactly the same. Figure 3 and attached Figure 4 It can be seen that the microstructure of the high-boron alloy prepared in Comparative Example 1 is mainly composed of austenite (γ-Fe), ferrite (α-Fe(M)), M2B phase, M 23 The volume fraction of the high boron alloy block phase is basically the same as that of Example 1, but there is no white Mo2FeB2 phase. 23 The number and morphology of (C, B)6 phase and TiC phase are basically the same. The average macroscopic hardness of the high-boron alloy is 58.6HRC, which is lower than 6.1HRC of the high-boron alloy shown in Example 1.

[0085] Compare with Figure 1 and attached Figure 3 It can be seen that although the volume fraction of the blocky main wear-resistant phase of the high boron alloy in Comparative Example 1 is substantially the same as that of Example 1, Example 1 has a Mo2FeB2 phase with high microhardness, which makes its macroscopic hardness higher.

[0086] Compare with Figure 5 and attached Figure 6 From the wear morphology of the two high-boron alloys shown, it can be seen that under the same wear test conditions, the high-boron alloy wear surface scratches prepared by the composite powder surfacing of the present invention are small and shallow, and the scratches are all intermittently distinguished; its spalling pits are shallow and small, and the overall wear is uniform, and its wear mechanism includes two types: micro-stripping and micro-cutting of abrasive particles. The wear surface scratches of the high-boron alloy shown in Comparative Example 1 are large and deep, and the length is significantly greater than the scratch length shown in Example 1; its spalling pits are deep and large, and the wear mechanism includes two types: micro-stripping and micro-cutting of abrasive particles. The weight loss from wear is significantly higher than that of the high-boron alloy prepared by the composite powder of the present invention, and is basically the same as the usual high-boron alloy. The above results show that the high-boron alloy surfacing welded by the composite powder of the present invention has extremely excellent wear resistance.

[0087] Compare with Figure 7 From the microscopic distribution diagram of the vertical cross section of the high boron alloy of the comparative example and Example 1, it can be seen that the microhardness of the surfacing high boron alloy of Example 1 is significantly higher than that of Example 1, and the microhardness of some areas can reach 1600-1700 HV, which is higher than the microhardness level of the traditional high boron alloy below 1200 HV, reaching the level of powder cemented carbide tools, especially the microhardness of the second layer has exceeded the microhardness of the blocky primary M2B phase of the traditional high boron alloy. This makes it have extremely excellent wear resistance and can be used for the surfacing preparation and repair of the tooth head and side of the single roller crusher for crushing high-temperature slag.

Claims

1. A composite powder for self-protected open arc surfacing welding of high-boron alloy, wherein the composite powder with a particle size of 8-10 mesh is prepared by the following preparation process steps: sieve weighing the powder components contained therein, dry mixing, wet mixing with water glass, wet powder rotary granulation, low-temperature sintering, and powder screening; the weight percentages of the powder components contained in the composite powder are as follows: 37-42% of ferromolybdenum with a molybdenum content of 48-52%; 20-22% of boron carbide with a boron carbide content of more than 99%; 10-12% of high-carbon ferrochrome with a chromium content of 68-72% and a carbon content of 8%; 9-11% of ferrotitanium with a titanium content of 25-30%; 2-3% of aluminum-magnesium powder with an aluminum content of 49-50% and a magnesium content of 49-50%; and the remainder is reduced iron powder with an iron content of not less than 98%.

2. The composite powder for self-shielded open arc surfacing of high-boron alloy according to claim 1, characterized in that: The powder components of ferromolybdenum, boron carbide, high carbon ferrochromium, ferrotitanium and reduced iron powder contained in the composite powder particles are passed through a 60-mesh sieve, and the aluminum-magnesium powder is passed through a 200-mesh sieve and then weighed.

3. The composite powder for self-shielded open arc surfacing of high-boron alloy according to claim 1, characterized in that: The water glass added to the dry mixed powder is of sodium silicate type, with a Baume degree of 30 to 35 and a modulus of 3.0 to 3.

3.

4. The composite powder for self-shielded open arc surfacing of high-boron alloy according to claim 1, characterized in that: Water glass was added to the dry mixed powder in an amount of 20 to 25 ml of sodium silicate type water glass per 100 g of the dry mixed powder for wet mixing.

5. The composite powder for self-shielded open arc surfacing of high-boron alloy according to claim 1, characterized in that: The rotation speed for bonding and granulating the wet powder is 2 to 4 revolutions per second.

6. The composite powder for self-shielded open arc surfacing of high-boron alloy according to claim 1, characterized in that: The composite powder particles are sintered at a low temperature of 280-300°C and kept warm for 2-4 hours before being taken out of the furnace.

7. A method for applying the composite powder as claimed in claim 1, characterized in that: Before welding, the screened composite powder particles are pre-placed on the weld bead, and the ER304 stainless steel solid welding wire with a diameter of Φ2.5mm is used as the filling material. The DC power supply reverse connection method is used for self-shielded open arc surfacing. The arc generated between the stainless steel solid welding wire and the substrate is used to melt the composite powder particles pre-placed on the weld bead, and the molten droplets together with the stainless steel solid welding wire form a surfacing pool, which is cooled and solidified into a high-boron alloy with a powder filling rate of 0.45 to 0.

50.

8. The method for applying the composite powder according to claim 7, characterized in that: The surfacing welding current control value is 410~420A, and the welding machine trolley travel speed is 15.5~16.0m / h.